Influenza-virus membrane fusion by cooperative fold-back of stochastically induced hemagglutinin intermediates - Ivanovic, Tijana; Choi, Jason L; Whelan, Sean P; van Oijen, Antoine M; Harrison, Stephen C (eLife, 2013)
Influenza virus penetrates cells by fusion of viral and endosomal membranes catalyzed by the viral hemagglutinin (HA). Structures of the initial and final states of the HA trimer define the fusion endpoints, but do not specify intermediates. We have characterized these transitions by analyzing low-pH-induced fusion kinetics of individual virions and validated the analysis by computer simulation. We detect initial engagement with the target membrane of fusion peptides from independently triggered HAs within the larger virus-target contact patch; fusion then requires engagement of three or four neighboring HA trimers. Effects of mutations in HA indicate that withdrawal of the fusion peptide from a pocket in the pre-fusion trimer is rate-limiting for both events, but the requirement for cooperative action of several HAs to bring the fusing membranes together leads to a long-lived intermediate state for single, extended HA trimers. This intermediate is thus a fundamental aspect of the fusion mechanism.
Keywords: influenza; enveloped virus; membrane fusion; single molecule; virus entry; lipid bilayer